Current issues of social network services - Le, Ho Cheong (Faculty of Computer Systems and Software Engineering, 2011)
The development and the application of Social Network Services have a great impact on the communication and social life [1]. This chapter looks specifically at the popular Social Network Services development around the world and highlights the major issues on the ways to use the services. The impact of those issues on communication and social life are explored. In addition, two specific cases are reported to reflect the implications of the importance on the appropriate ways to use the services.